Comparative transcriptomic analysis highlights contrasting levels of resistance of Vitis vinifera and Vitis amurensis to Botrytis cinerea. (1st May 2021) - Wan, Ran; Guo, Chunlei; Hou, Xiaoqing; Zhu, Yanxun; Gao, Min; Hu, Xiaoyan; Zhang, Songlin; Jiao, Chen; Guo, Rongrong; Li, Zhi; Wang, Xiping
Abstract: Botrytis cinerea is a major grapevine ( Vitis spp.) pathogen, but some genotypes differ in their degree of resistance. For example, the Vitis vinifera cultivar Red Globe (RG) is highly susceptible, but V. amurensis Rupr Shuangyou (SY) is highly resistant. Here, we used RNA sequencing analysis to characterize the transcriptome responses of these two genotypes to B. cinerea inoculation at an early infection stage. Approximately a quarter of the genes in RG presented significant changes in transcript levels during infection, the number of which was greater than that in the SY leaves. The genes differentially expressed between infected leaves of SY and RG included those associated with cell surface structure, oxidation, cell death and C/N metabolism. We found evidence that an imbalance in the levels of reactive oxygen species (ROS) and redox homeostasis probably contributed to the susceptibility of RG to B. cinerea . SY leaves had strong antioxidant capacities and improved ROS homeostasis following infection. Regulatory network prediction suggested that WRKY and MYB transcription factors are associated with the abscisic acid pathway. Weighted gene correlation network analysis highlighted preinfection features of SY that might contribute to its increased resistance. Moreover, overexpression of VaWRKY10 in Arabidopsis thaliana and V. vinifera Thompson Seedless enhanced resistance to B. cinerea . Collectively, our study provides a high-resolution view of the transcriptional changes of grapevine in response to B. cinerea infection and novel insights into the underlying resistance mechanisms.